(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This scientific article describes the issues of improving the organizational and legal basis of search and rescue operations in the Republic of Uzbekistan. Also, problems encountered in the field of rapid search operations and proposals for their solution are described